Implementasi Kebijakan Akreditasi Rumah Sakit Dalam Pelayanan Kesehatan pada Rumah Sakit Umum Daerah Pandau Tambuh Kabupaten Donggala - Tofan, Tofan; Mufti, Irfan; Asrifai, Asrifai (CV. Rayyan Dwi Bharata, 2025)
The results of this study show that the implementation of the accreditation policy at Pandau Tambu Hospital is quite optimal, this is supported by clear standards and objectives and high commitment from various parties, but faces challenges in resources and coordination that need to be resolved. Aspects of Standards and Policy Objectives, where the main goal of the accreditation policy of Pandau Tambuh Hospital is to improve the quality, safety, and trust in health services in accordance with national standards (KARS). The standards applied have been measured through the hospital's vision, mission, and accreditation indicators. The aspect of resources, which is a determining factor in implementation. In practice, the Pandau Tambu Regional General Hospital continues to strive to improve its competencies and infrastructure (e.g. intensive training and evaluation of facilities), but budget constraints are the main challenges that require more attention. Aspects of the Characteristics of the Implementing Agency, where the Donggala Regency Health Office and Pandau Tambuh General Hospital are committed to forming a responsive organization, focus on quality, and a solid work team, although coordination between units still needs to be strengthened. It was found that the accreditation team is highly committed, but it is necessary to strengthen a disciplined work culture and a good data management system. The aspect of the Attitude of the Implementer, where the accreditation team and employees of Pandau Tambu Hospital display a high spirit of change, although it is recognized that a more structured work culture is needed. The aspect of communication between organizations and activity implementers has not gone optimally where there is weak communication between the internal units of Pandau Tambuh Hospital, especially in the administration and logistics sections. The Economic, Social, and Political Aspects, are going quite well where the Donggala Regency Government fully supports the implementation of Accreditation at the Dearah Pandau Tambuh General Hospital, it's just that from the economic and social aspects it still needs more attention.